A proteção dos direitos autorais a partir da realidade Internet: a perspectiva brasileira - Sola, José Eduardo Martins [UNESP] (Universidade Estadual Paulista (Unesp), 2002)
The Internet has been substantially changing the research habits of human beings, on one hand providing them more agility and efficiency for obtaining information, but on the other hand it increases problems related to copyright in works that the net can spread. Consequently, it is necessary to analyse, in Brazilian doctrinal, legislative and jurisprudencial scopes the copyright (intellectual and material) and its apply to the creations on the net, to which are related questions such as the control of publications copies and the means to avoid falsifications, adulterations and inappropriate use of them. Based on documentary research, on law and also on information from the net, starting from the Internet approach in its concept, characteristics and types of documents, it is analysed the copyright in theoretical (concept and kinds) and applied (control and protection in Brazilian law) terms and it is discussed the use of some elements to protect copyright on the Internet: Cryptography, Digital Subscription, Digital Certification and Digital Watermark, and it is concluded with the diplomatic nature of the same. It is verified that the Cryptography, as a code, is the language through which the document is presented, and it can be characterized, among the elements that form the documentation structure, as an outer element, under the diplomatic view. The Digital Signature characterizes a subscription, that is, the author's signature on digital documents, it is therefore, featured as an element of the document inner structure. The Digital Certification represents a kind of precation because it proves the legality of the document. This tool is compared to a validating sign or to a testifying signature, being featured by diplomatic as an inner element of the documentation structure. Finally, it is verified that the Digital Watermark is compared to a special... (Complete abstract, click electronic address below)

A Internet vem modificando substancialmente os hábitos de pesquisa do ser humano, por um lado permitindo-lhe maior agilidade e eficiência na obtenção de informações, mas, por outro, multiplicando problemas de direito autoral nas obras por ela veiculadas. Desse modo, torna-se necessário analisar, no âmbito doutrinário, legislativo e jurisprudencial brasileiro, os direitos autorais (intelectuais e materiais) e sua aplicabilidade às criações dispostas na rede, ao que se aliam questões como a de controle das cópias de tais publicações e a de meios para evitar falsificações, adulterações e uso indevido das mesmas. Valendo-se de pesquisa documental em fontes do direito e em informações da própria rede, parte-se da abordagem da Internet em seu conceito, características e tipos de documentos, analisam-se os direitos autorais em termos teóricos (conceito e modalidades) e aplicados (controle e proteção no Direito Brasileiro) e discute-se a utilização de alguns elementos para a proteção dos direitos autorais na Internet: Criptografia, Assinatura Digital, Certificação Digital e Marca d'Água Digital, concluindo-se pela natureza eminentemente diplomática dos mesmos. Verifica-se que a Criptografia, enquanto código, é a linguagem por meio da qual se apresenta o documento, podendo ser caracterizada, dentro dos elementos que compõem a estrutura documental, como um elemento externo, sob a ótica diplomática. Já a Assinatura Digital caracteriza uma subscrição, ou seja, a assinatura do autor nos documentos digitais, sendo dessa forma caracterizada como um elemento de estrutura interna do documento. A Certificação Digital representa uma espécie de precação, pois é por seu intermédio que se tem a certeza da legalidade do documento. Essa ferramenta é comparada a um sinal de validação ou uma assinatura testemunhal, ficando, assim...
Keywords: Direitos autorais - Brasil; Internet; Redes de computadores; Internet; Copyright; Copyright Protection; Copyright in Brazil